Dragonflies (Insecta, Odonata) of the «Khomutovskaya Steppe» Nature Reserve - Vladimir V. Martynov; Tatyana V. Nikulina (Nature Conservation Research: Заповедная наука, 2017)
A review and comparative analysis of the Odonata fauna from the Khomutovskaya Steppe Reserve including nature conservation areas of the northern territories of the Sea of Azov (within Donbass) are given. 28 species of 14 genera from the six families are listed for the Reserve and its protected territories. The Khomutovskaya Steppe Reserve is suggested as a monitoring centre for the dragonfly fauna of the Cis-Azov region.